The Diabetic Neuropathies: Practical and Rational Therapy - Singleton, J. Robinson; Smith, A. Gordon (Seminars in Neurology, 2012)
Diabetes is associated with a variety of chronic and acute neuropathies. In this article, the authors summarize the clinical features of the most common diabetic neuropathies, focusing on those for which therapy is available or under active investigation. Distal symmetric polyneuropathy (DSP) is the most common form. Potential treatments for DSP are discussed in four broad themes: (1) medication and lifestyle therapy to improve hyperglycemia, insulin resistance, and attendant features of metabolic syndrome, including obesity and dyslipidemia; (2) pharmacologic therapy to alter neuropathy natural history aimed at rational targets from known pathophysiology; (3) symptomatic relief of neuropathic pain; and (4) treatment to prevent complications of neuropathy, including stasis ulcers and falls. The approach to the most common acute diabetic neuropathies is also reviewed.
Keywords: diabetes; peripheral neuropathy; diabetic amyotrophy